2007
DOI: 10.1016/j.ijgo.2006.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Detection and typing of minimal human papillomavirus DNA in plasma

Abstract: The high sensitivity and accuracy of this method has allowed detection of HPV in specimens of minimal viral load, such as in plasma in peripheral circulation of cervical cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
14

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 17 publications
0
26
0
14
Order By: Relevance
“…HPV-16 and HPV-18 types of HPV are present in approximately 70% of primary tumors [183][184][185]. In contrast to NPC, the potential application of serum / plasma HPV DNA in cervical cancer has not been investigated systematically.…”
Section: Viral Dna In the Circulationmentioning
confidence: 99%
See 1 more Smart Citation
“…HPV-16 and HPV-18 types of HPV are present in approximately 70% of primary tumors [183][184][185]. In contrast to NPC, the potential application of serum / plasma HPV DNA in cervical cancer has not been investigated systematically.…”
Section: Viral Dna In the Circulationmentioning
confidence: 99%
“…Yang et al by means of quantitative PCR have found the incidence of plasma HPV-16/HPV-18 increased to 64.3% in the cases positive for HPV in their primary tumors [184]. The sensitivity of HPV DNA assay was shown to be increased using nested PCR method, which detected a broad spectrum of at least ten genital types of HPV with a sensitivity of one viral copy [183]. HPV DNA was detectable in 65% of the patient plasma, from which the genotype was successfully determined in 9 cases, all identical to that of primary cancer tissue.…”
Section: Viral Dna In the Circulationmentioning
confidence: 99%
“…Prior studies of circulating HPV DNA in cervical cancers have reported a pre-treatment detection rate ranging from 12% to 65% and the positivity rate is highly dependent on the patient population and the assay. (19-23) Only one study has evaluated circulating HPV DNA in HNSCC, using a combination of conventional PCR, southern blot hybridization and quantitative PCR (qPCR). (24) In this study, Capone et al were able to detect E6/7 HPV DNA in 6 of 13 patients (46%) with HPV16(+) tumor.…”
Section: Introductionmentioning
confidence: 99%
“…There aren't any reports as how the virus is able to infect other organs; two mechanisms though, have been proposed: a mechanical path where the virus is scrubbed through the skin [25], and a systemic path where HPV spreads through the bloodstream by organ perfusion [36]. Whether any or both mechanisms are responsible for HPV propagation is not clear, HPV DNA has been found in plasma of patients with diagnosis of cervical cancer [37][38][39][40], and in sera of patients with breast cancer [24] and with HPV-associated head and neck squamous cell carcinoma [41]. Another reason for the few positive detected is the differential selective advantage given to the neoplastic cells by HPV and the relative number of infected cells within the clone pool.…”
Section: Discussionmentioning
confidence: 99%